ALUMINUM-26 IN H4 CHONDRITES: IMPLICATIONS FOR ITS PRODUCTION AND ITS USEFULNESS AS A FINE-SCALE CHRONOMETER FOR EARLY SOLAR SYSTEM EVENTS - Zinner E.; Göpel C. (My University, 2002)
In order to investigate whether or not 26Al can be used as a fine-scale chronometer for early solar system events we measured, with an ion microprobe, Mg isotopes and Al/Mg ratios in separated plagioclase, olivine, and pyroxene crystals from the H4 chondrites Ste Marguerite (SM), Forest Vale (FV), Beaver Creek and Quenggouk and compared the results with the canonical 26Al/27Al ratio for calcium-aluminum-rich inclusions (CAIs). For SM and FV, Pb/Pb and Mn-Cr ages have previously been determined (Göpel et al., 1994; Polnau et al., 2000; Polnau and Lugmair, 2001). Plagioclase grains from these two meteorites show clear excesses of 26Mg. The 26Al/27Al ratios inferred from these excesses and from isotopically normal Mg in pyroxene and olivine are (2.87 ± 0.64) × 10−7 for SM and (1.52 ± 0.52) × 10−7 for FV. The differences between these ratios and the ratio of 5 times 10−5 in CAIs indicate time differences of 5.4 ± 0.1 Ma and 6.1 ± 0.2 Ma for SM and FV, respectively. These differences are in agreement with the absolute Pb/Pb ages for CAIs and SM and FV phosphates but there are large discrepancies between the U-Pb and Mn-Cr system for the relative ages for CAIs, SM and FV. For example, Mn-Cr ages of carbonates from Kaidun are older than the Pb/Pb age of CAIs. However, even if we require that CAIs are older than these carbonates, the time difference between this “adjusted” CAI age and the Mn-Cr ages of SM and FV require that 26 Al was widely distributed in the early solar system at the time of CAI formation and was not mostly present in CAIs, a feature of the X-wind model proposed by Shu and collaborators (Gounelle et al., 2001; Shu et al., 2001). From this we conclude that there was enough 26Al to melt small planetary bodies as long as they formed within 2 Ma of CAIs, and that 26Al can serve as a fine-scale chronometer for early solar system events.